Involvement of GABAB Receptor Signaling in Antipsychotic-like Action of the Novel Orthosteric Agonist of the mGlu4 Receptor, LSP4-2022 - Woźniak, Monika; Acher, Francine; Marciniak, Marcin; LasoŦ#132;-Tyburkiewicz, Magdalena; Gruca, Piotr; Papp, Mariusz; Pilc, Andrzej; M. WieroŦ#132;ska, Joanna (Current Neuropharmacology, 2016)
Considering that ligands of metabotropic glutamate and GABA receptors may exert beneficial effects on schizophrenia, we assessed the actions of the first mGlu4-selective orthosteric agonist, LSP4-2022, in several tests reflecting positive, negative, and cognitive symptoms of schizophrenia. Moreover, we investigated the possible involvement of GABAB receptors in LSP4-2022-induced actions. Hyperactivity induced by MK-801 or amphetamine and DOI-induced head twitches in mice were used as the models of positive symptoms. The social interaction test, modified forced swim test (FST), and novel object recognition (NOR) test were used as the models of negative and cognitive symptoms of schizophrenia. LSP4-2022 inhibited hyperactivity (in a dose-dependent manner, 0.5-2 mg/kg) induced by MK-801 or amphetamine and DOI-induced head twitches. In mGlu4 receptor knockout mice, LSP4-2022 was not effective. However, it reversed MK-801-induced impairment in the social interaction test and the MK-801-induced increase of immobility in the modified FST. In the NOR test, LSP4-2022 was active at a dose of 2 mg/kg. GABAB receptor antagonist, CGP55845 (10 mg/kg), reversed LSP4-2022-induced effects in hyperactivity and head twitch tests. At the same time, the simultaneous administration of subeffective doses of LSP4-2022 (0.1 mg/kg) and a positive allosteric modulator of GABAB receptor PAM, GS39783 (0.1 mg/kg), induced clear antipsychotic-like effects in those two tests. Such an interaction between mGlu4 and GABAB receptors was not observed in the social interaction and NOR tests. Therefore, we suggest that the activation of the mGlu4 receptor is a promising approach facilitating the discovery of novel antipsychotic drugs, and that the interplay between mGlu4 and GABAB receptors may become the basis for a novel therapy for schizophrenic patients with predomination of positive symptoms.
Keywords: schizophrenia